Analyzing the Meaning of Language Use in Politeness Strategies in the Danish Girl Movie - Melati, Rahma; Sabaruddin (JLE: Journal of Literate of English Education Study Program, 2022)
Politeness strategies are used to craft messages that save the listener's positive and negative face when face-threatening behavior is inevitable or desired. Brown and Levinson mainly outline his four types of politeness strategies. Do not use baldness, negative politeness, positive politeness, off the record (indirect), and simply face-threatening behavior. Positive politeness strategies try to minimize threats to the listener's positive face and make the listener feel good. Negative politeness strategies are based on avoidance and assume that the speaker is imposing something on the listener. Off-the-record strategies use indirect speech to deprive the speaker of the possibility of imposing themselves on the listener. Discourse analysis is conducted to analyze the "face-threatening acts" (FTA) in some conversations of The Danish Girl Movie(2015). Positive politeness or negative politeness is adopted to examine how to speaking between man and a beautiful girl respectively in unconventional ways, which enable them to develop friendship thanks to the politeness strategies used positive politeness and negative politeness. The "meaning of language use" in the politeness strategies is explored. The analysis of politeness in action in this film uncovers both the informational and affective dimensions of language use in structuring human relationship and friendship. Data were analyzed using the content analysis method. In this paper, used a purposive sampling technique. With this technique, only utterances with positive and negative politeness strategies were selected for inclusion in this paper. A descriptive qualitative research technique was used to analyze the data. Guidance maps were used to identify positive and negative politeness strategies. The study found that use positive and negative politeness strategies to mitigate threats. It also helps interlocutors understand the strategies they can use to communicate effectively, ensuring both sides feel valued in the conversation.